Becoming, Doing, Being and Belonging into Academics: Career Trajectories of Early-Career Academics at the University of Dar es Salaam - Kayombo, Joel Jonathan (Papers in Education and Development, 2020)
Using a qualitative phenomenological case study, this paper analyses the dynamics and complex experiences of early career academics (ECAs) within the increasingly neoliberal university, the University of Dar es Salaam. It employed focus group discussion and in-depth individual interview methods for data collection from 21 participants. Davey ' s framework was used to access and analyse the participants ' narrative accounts. The findings demonstrate that neoliberal- driven reforms have affected and continue to affect the lives of the ECAs. Their lives have been dominated by constant struggles to develop professionally within the neoliberal context. The study recommends the university to make concerted efforts to assist ECAs ' professional development through establishing mentoring programmes and ensuring a balance between teaching load and other core activities. Keywords: higher education, neoliberalism, phenomenology, professional experiences, reflexivity